Examining English Teachers’ Lesson Plans: A Content Analysis of Higher-Order Thinking Skill Integration - Ema Meida Tunnadia; Nur Syuhada Binti Mohd Rashid (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2025)
This study investigates the extent and nature of higher-order thinking skill (HOTS) integration in English teachers’ lesson plans within English as a Foreign Language (EFL) context. Using Bloom’s Revised Taxonomy as the analytical framework, the research employed a qualitative content analysis of 12 lesson plans drawn from secondary and tertiary English teachers in Indonesia. The analysis focused on identifying the presence and types of cognitive processes embedded in learning objectives, instructional activities, and assessments. The findings reveal a predominant emphasis on lower-order thinking skills (LOTS), particularly understanding and applying, while HOTS—such as analyzing, evaluating, and creating—were included less frequently and often lacked alignment across instructional components. Among the HOTS categories, analyzing appeared most commonly, whereas evaluating and creating were significantly underrepresented. This suggests a limited instructional emphasis on critical and creative thinking development in EFL lesson planning. The study concludes that while teachers may recognize the importance of fostering HOTS, structural, curricular, and pedagogical constraints often hinder their consistent implementation. Limitations of the study include the small sample size and exclusive reliance on document analysis. Future research should incorporate classroom observations and teacher interviews to gain a more holistic understanding of how HOTS are operationalized in practice.